An audit of the integrated treatment unit at Sterkfontein Psychiatric Hospital - Maynard, Fiona (My University, 2020)
Aim: To conduct an audit of this unit with a view to: 1) describe the demographic characteristics of users, 2) describe the clinical profile of users, and 3) determine, if any, differences between the psychotic and mood disorder groups with respect to demographic and clinical characteristics. Hypothesis: Patients with psychotic disorders are more likely to be younger, have recurrent admissions and abuse cannabis more often than other substances, when compared to people diagnosed with mood disorders. Method: The study is a descriptive, retrospective record review of all patients admitted to the Integrated Treatment Unit at Sterkfontein Psychiatric Hospital for a period of one year from inception. Data was analysed using statistical principles and computations. Results: There were 74 participants with a mean age of 29 years. The majority were Black (69%) males (92%). 65% completed at least a grade 10 level of education, of which 75% were unemployed but 19% were supported financially by their families. 91% were single but had a support structure in 68% of cases. 36% had a positive family history of mental illness and 36% a positive family history of substance abuse. 57% presented with a previous criminal history. Cannabis (92%) and alcohol (83.8%) were the most common substances abused. Participants presented with mood disorders predominantly (40,5%) and 29.7% with psychotic disorders. 31,1% were on a combination of an antipsychotic and anticonvulsant medication. 68.9% of patients fulfilled criteria for substance dependence. Conclusion: More young people with mood disorders present with dual diagnoses. The majority used cannabis and alcohol as their main substance of abuse whilst more than half of participants fulfilled criteria for substance dependence. It is hoped that further local research into this topic will improve outcomes for vulnerable patients with complex and often difficult to diagnose and treat dual diagnoses.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Psychiatry to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020